Epileptic seizures caused by encephalomalasic cysts following radiotherapy: A case report - Erol, Fatih Serhat; Akgun, Bekir (My University, 2009)
Introduction: Cerebral radionecrosis is a delayed and rarely observed complication of radiotherapy. Cerebral radionecrosis may occur as cystic encephalomalasic formations which cover the intracranial region. These cysts may, in rare cases, become quite large. They may cause drug-resistant seizures, neurological deficits and consciousness disorders. Case presentation: A 55-year-old, Turkish female patient was admitted to hospital with seizure, consciousness disorder and weakness in the right side of her body. The patient had history of an operation in the left maxillary area due to basal cell carcinoma 7 years previously and then history of radiotherapy due to relapse 2 years later the operation. The patient had large cystic encephalomalasic lesions. Despite steroid and dual antiepileptic treatments, the patient's complaints had significantly worsened and seizures continued. Surgical treatment resulted in a significant improvement. Conclusion: This report underlines the significance of surgery in cerebral radionecrosis treatment in well-selected cases using appropriate approaches. © 2009 Erol and Akgun; licensee Cases Network Ltd.
Keywords: phenytoin; steroid; valproic acid; adult; anamnesis; article; brain cyst; cancer radiotherapy; case report; cognitive defect; craniotomy; electroencephalography; encephalomalasic cyst; female; follow up; hemiparesis; human; muscle strength; neuroimaging; neurologic examination; papilledema; radiation necrosis; speech disorder; tonic clonic seizure